Frequency and survival of Covid associated mucormycosis patients at tertiary care hospitals in Pakistan: A retrospective observational study. Issue 2 (3rd February 2023) - Irfan, Ayesha; Kamran, Afshan Hussain; Ammar, Muhammad; Rahman, Saeed ur
Abstract: Background: Mucormycosis is a serious fungal infection associated with uncontrolled diabetes and immunocompromised patients. This angioinvasive infection emerged as a post‐covid complication worldwide especially in developing countries. Due to the common socio‐demographic status of South Asian countries, we expected a surge in mucormycosis cases in Pakistan. This study aims to observe the frequency and survival of Covid associated mucormycosis patients at tertiary care hospitals in Pakistan during the third wave of Covid‐19 in 2021. Materials and Methods: In this retrospective study, we collected the data of clinically and histopathologically confirmed cases of rhino‐occipito‐cerebral mucormycosis from three tertiary care hospitals of Lahore. These cases were analysed for history of Covid‐19 and other associated comorbidities using SPSS28. History of steroid medication was also taken. Data were retrieved from May to July 2021 after the approval from the ethical review board. Results: Out of the total 43 reported patients of mucormycosis in the set time frame only 22 cases had a history of Covid‐19. The mean age was 50 ± 13.27 years with slight male predilection (60%). Diabetes mellitus was the most common comorbidity (88.4%) and all the patients with covid associated mucormycosis (CAM) had taken corticosteroid regimen for covid management ( p  < 0.0001). The survival of the patient was not significantly different between CAM and non‐CAM patients of Mucormycosis ( p  = 0.747). Conclusion: Covid‐19 and mucormycosis make a lethal duo against the weakened health system of Pakistan. This problem can be prevented by avoiding nonjudicial use of corticosteroids and proper diabetes control program following Covid‐19 infection. Furthermore, large‐scale epidemiological studies should be carried out to evaluate the true burden of Mucormycosis in the population.